EPIDEMIOLOGY, ETIOPATHOGENESIS, AND HEMOSTASIS PROCEDURES IN RECURRENT EPISTAXIS - O. NEMATZODA; Z.A. AKHROROVA; D.D. SULTANOV; I. UBAYDULLO (Avicenna Tajik State Medical University, 2024)
Objective: To examine the literature on epidemiology, etiology, and treatment strategies for recurrent nosebleeds (RNB, epistaxis). Methods: Using information portals and platforms, including Elibrary.ru, PubMed, Web of Science, and Cochrane.org, we searched for specific keywords related to epistasis, including nosebleeds, recurrent nosebleeds, etiology, hemostasis methods, epistaxis, recurrent epistaxis, epidemiology, etiology, pathogenesis, treatment. We analyzed sixty-eight English and Russian scientific papers, excluding RNB articles on blood diseases, cancer, nasal injuries, and post-surgical interventions. Results: The prevalence rate of RNB remains unknown, with studies focusing on single institutions or regions. Epistasis relapse rates range from 5.9% to 30.5%, varying by cause and treatment methods. Most cases involve anterior epistaxis (90%), while 12.4% to 34.8% experience more severe posterior bleeding. Factors like arterial hypertension (AH), anticoagulant use, and environmental factors contribute to RNB. Severe cases may require hospitalization (6% to 8.2%), with 10.7% facing a third relapse needing vessel ligation or embolization. Around 0.25% to 4.8% of RNB patients may succumb due to complications or excessive bleeding. Conclusion: Research focused on understanding the reasons and procedures for treating RNB remains essential, as the condition can be life-threatening. Recurrence of epistaxis after different RNB treatments may require more extreme vessel-ligating surgeries. Therefore, improving treatment outcomes by adopting a personalized approach to selecting hemostasis methods and addressing the underlying causes of RNB is crucial.